Inheritance and fitness costs of sulfoxaflor resistance in Nilaparvata lugens (Stål). Issue 11 (12th April 2019) - Liao, Xun; Mao, Kaikai; Ali, Ehsan; Jin, Ruoheng; Li, Zhao; Li, Wenhao; Li, Jianhong; Wan, Hu
Abstract: BACKGROUND: Sulfoxaflor has been considered as a new tool for Nilaparvata lugens control in the field. In this study, a laboratory‐selected resistant strain and a susceptible strain were used to evaluate the inheritance and fitness costs of sulfoxaflor resistance in N. lugens . RESULTS: The resistant strain (SFX‐SEL) showed 123.63‐fold resistance compared with the susceptible strain (SS). Progenies of reciprocal crosses (F1 RS and F1 SR) showed similar concentration–mortality responses (LC50 ) to sulfoxaflor and also exhibited a similar degree of dominance; −0.16 for F1 RS and −0.26 for F1 SR. Significant differences between the observed and expected mortalities of F2 individuals suggested that sulfoxaflor resistance is associated with multiple genes. The resistant strain had a relative fitness of 0.75 with substantially decreased female adult period, oviposition days, total fecundity, egg hatchability and female adult survival rate, and prolonged pre‐adult period and total pre‐oviposition period. CONCLUSION: Sulfoxaflor resistance in N. lugens was inherited as autosomal, incompletely recessive and multigene. The development of resistance may have a significant fitness cost for the resistant population. Current research provides valuable information for researchers to establish management strategies to delay the development of sulfoxaflor resistance and control N. lugens sustainably in the field. © 2019 Society of Chemical Industry Abstract : Sulfoxaflor resistance in Nilaparvata lugens was inherited as autosomal, incompletely recessive and multigene. Development of resistance may have a significant fitness cost for the resistant population.